Parallel operation of transformers to optimize a 33 KV loop of power system - Arbih Mahmoud, Ethmane Isselem; Abbou, Ahmed; Mahmoud, Abdel Kader (International Journal of Applied Power Engineering (IJAPE), 2025)
This research investigates the viability of a perpetually scalable generation system to accommodate the anticipated growth in domestic load demands on the 33 kV loop network over the period from 2025 to 2040. This is achieved by analysis current situation of network through the voltages, loading lines, and transformers, within the permissible loading limits of the system. In this context, it is assumed that the loop is supplied by an ideal infinite power source. A numerical model utilizing the Gauss-Seidel (GS) method is developed and executed within the PSS/E simulator. The current operational state of the network will be simulated, with a focus on analyzing the voltage profile, which is expected to remain within the range of 0.095 to 1.05 per unit (p.u.). Demand forecasts are based on industrial growth projections for the cities interconnected with the 33 kV loop. The simulation results will demonstrate the feasibility of increasing active power transmission while maintaining effective control over reactive power by the year 2040. Furthermore, solutions will be proposed to address the identified critical path issues. To meet the projected demand, these solutions will involve doubling the capacity of the existing transformers. The proposed system will mitigate load imbalances and stabilize voltage fluctuations by effectively managing rapid variations in reactive power demand. As a result, it improves power quality for industrial consumers.